2006
DOI: 10.1177/0305735606064839
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of creativity and musical experience

Abstract: This preliminary investigation examined the relationship between creative personality traits and musical experience. Creative personality traits were hypothesized to be positively correlated with musical experience. Two self-report measures, the Creative Personality Scale and the Scale of Musical Experience, were designed for this study. Initial analyses showed that both measures designed for this study were reliable and valid. Students ( n = 150) from Introduction to Psychology and Music classes participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
0
20
0
7
Order By: Relevance
“…The second test was the Creative Personality Scale, designed by Goncy and Waehler (2006), for a study on the relationship between creativity and musical experience. The questionnaire includes 30 statements (such as: ''I find myself capable of handling a variety of situations''; and ''I do well at synthesizing materials from many different parts of my life'').…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second test was the Creative Personality Scale, designed by Goncy and Waehler (2006), for a study on the relationship between creativity and musical experience. The questionnaire includes 30 statements (such as: ''I find myself capable of handling a variety of situations''; and ''I do well at synthesizing materials from many different parts of my life'').…”
Section: Methodsmentioning
confidence: 99%
“…The mean score on this scale was 121.94, SD ¼ 13.67. Scores for the 3 subscales described in Goncy and Waehler (2006) were computed for each participant. Reliability for the first factor, named problem solving, was .844.…”
Section: Creative Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study also suggested that people with Agreeableness and Conscientiousness traits were likely to choose less expressive music (less emotional, very concrete thoughts and ideas) and be less actively involved. This is supported by a positive correlation that exists between creative personality traits and musical experience, forming yet more foundation for the study at hand (Goncy & Waehler, 2006).…”
mentioning
confidence: 87%
“…Research on creative students and other studies that complement the four-fold framework Some recent music research enquiries have as a principal focus the characteristics of creative students (Goncy and Waehler, 2006) or the commonalities regarding some of the environment, process and product areas, such as learning strategies using IT, group processes and assessment (Folkestad, 2004). A number of other studies have complemented the four-fold framework with the analysis of 'creative teaching practices' in the context of a secondary music teacher education course in England (Alsina, 2006) and with philosophical considerations of the meaning of creativity in music education (Humphreys, 2006).…”
Section: Recent Studies On the Composing And Improvising Processesmentioning
confidence: 99%